In Vitro Effciacy Of Different Botanicals And Chemicals Against Xanthomonas Citri (Journal of Plant Disease Sciences, 2020)
In vitro efficacy of botanicals and different chemicals against Xanthomonas citri subsp. citri was assessed. Among the plant leaf extracts Azardiricta indica found most effective in alcoholic extracts by developing 13.45 mm, 11.70 mm, 10.12 mm and 8.2 mm of inhibition zone at 20% 15%, 10% and 5% concentration respectively. In respect of fruits extracts, alcoholic extract Garcinia indica gives highest inhibition zones 17 mm, 15.0 mm, 6.9 mm and 0 mm at tested concentrations whereas in flower extracts, Lathyrus odoratus found superlative as highest inhibition zones 13.14 mm, 9.23 mm, 8.00 mm and 6.23 mm registered at tested concentrations. Among the extracts of different vegetative parts of plants, alcoholic extract of Allium sativum produced highest inhibition zones 16.20 mm, 13.40 mm, 7.23 mm and 0.00 mm at 20% 15%, 10% and 5% concentrations respectively. In case of chemicals, significantly highest zone of inhibition recorded with streptomycin sulphate at 100, 250 and 500 ppm concentration followed by bromopol and kasugamycin.
Keywords: Canker; Xanthomonas citri; botanicals; Chemicals and inhibition